CONVERSION OF MASK WASTE INTO LIQUID FUEL USING PYROLYSIS PROCESS - Ramadhana Putra, Aldy
During the Covid-19 pandemic, people are required to wear masks when doing activities outside the home. Therefore, during pandemic, the need for masks has increased very high, especially for disposable masks. The extensive use of disposable masks can lead to a buildup of mask waste, increasing the risk of disease transmission. In this final project, the conversion of mask waste into liquid fuel using the pyrolysis process was carried out. Laboratory-scale pyrolysis testing has been done within a temperature range of 440 – 500 °C and atmospheric pressure, followed by testing the characteristics of the resulting liquid pyrolysis products such as density, viscosity, and higher heating value. An assessment of energy self-sufficiency from the pyrolysis process of mask waste was also conducted. The experimental results showed that the optimum operating parameter was at a temperature of 460 °C because it produces pyrolysis oil of the highest yield and heating value. The liquid product produced from the pyrolysis process had a density of 784.8 kg/m3 , dynamic viscosity of 0.87 cP, kinematic viscosity of 1.10 cSt, and higher heating value of 45.06 MJ/kg. To achieve energy self-sufficiency, the pyrolysis process required a minimum of 200 grams of mask samples in the reactor used in this experiment. The pyrolysis oil at the optimum operating temperature had characteristics closer to gasoline (Pertamax) in terms of density, carbon chain range, and heating value. The viscosity value of the pyrolysis oil on the other hand was closer to that of kerosene; thus it can be utilized as an alternative fuel for direct combustion. This proves that the pyrolysis process will be able to overcome the problem of accumulated mask waste by producing useful liquid fuel in a self-sustaining process.